Engineering the Maltose Binding Protein for Metal Ions Sensing - Shahir, Shafinaz; Cass, Tony (2005)
The detection and quantification of metal ions remains a major environmental concern. Whilst conventional methods routinely used for metal ion detection are reliable, the true toxicity of samples to biological systems is not known since the amount of bioavailable metal is not taken into account. Alternative measuring devices which use biological molecules as the sensing element (biosensors) appear to be ideal for the measurement of metal ion levels in the field as they could provide an indication of the bioavailability of at least some metals. Here we report the development of an array-based sensor for the detection of metal ions using variants of the maltose binding protein (MBP) as the biorecognition element. MBP is a member of the periplasmic binding proteins that typically adopt two conformations: an open and closed form upon ligand binding. This ligand-mediated conformational change forms the basis of the sensing system. An impending issue in protein microarray technologies is the efficient immobilisation of proteins in an active state onto glass surfaces. This study exploits one of the strongest non-covalent interactions known in nature, that of biotin and avidin (KD of 10-15 M), as a method for protein immobilisation. A biotin tag was introduced to the C-terminus of the cytoplasmic form of MBP (cMBP). Two cysteine mutants of the cMBP (D95C and S337C) were made by site-directed mutagenesis. The biotin-tagged cMBP and the corresponding cysteine mutants were successfully expressed and biotinylated in vivo in Escherichia coli cells engineered to overexpress the biotin protein ligase. The response of IANBD labeled-biotinylated cysteine mutants to maltose binding was assessed via steady-state fluorescence. Three metal-binding site designs (M1, M2 and M3) based on a tetrahedral primary coordination sphere consisting of histidines and/or glutamates were each engineered into the receptor pocket of the MBP using site-directed mutagenesis. The affinities of the M1, M2 and M3 sites to maltose and to transition metal ions such as Zn2+, Cu2+, Co2+, Ni2+, Mn2+, Cd2+, Ag+ were tested in solution on a microtiter plate arrangement. Nanoliter volumes of the variants have been spotted onto streptavidin-coated glass slides and work is ongoing to evaluate the arrayer produced for metal ions sensing.